The Role of Learning Motivation as a Mediator of Parental Social Support and Self-Concept on Students’ Learning Achievement at State Vocational High School 3 Jakarta - Saputri, Hanifah Ria; Nurmalasari, Dewi; Fauzi, Achmad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study examines and analyzes the mediation of learning motivation as a mediation of parental social support and self-concept of student learning achievement at SMK Negeri 3 Jakarta. This study uses a data collection method through distributing questionnaires and documenting report card scores. The population studied was 215 class X students at SMK Negeri 3 Jakarta in the 2024/2025 academic year. The data analysis method used in this study is the Structural Equation Model (SEM) using Partial Least Square (PLS). Data analysis techniques using Smart PLS application software version 4.0.9 2024. The results of the study are as follows: (1) Parental Social Support has a positive and significant effect on student Learning Achievement, (2) Self-Concept does not have a positive and significant effect on student Learning Achievement, (3) Parental Social Support has a positive and significant effect on student Learning Motivation, (4) Self-Concept has a positive and significant effect on Learning Motivation, (5) Learning Motivation has a positive and significant effect on student Learning Achievement, (6) Learning motivation does not mediate the effect of Parental Social Support on Learning Achievement, (7) Learning motivation mediates the effect of Self-Concept on Learning Achievement. This study clarifies that the factors that can develop student learning achievement at SMK Negeri 3 Jakarta are parental social support, self-concept and good learning motivation.